2020
DOI: 10.3390/jcm9051596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Gut Microbiota on Atorvastatin Mediated Effects on Blood Lipids

Abstract: Background and Aims: The mechanisms of interindividual variation of lipid regulation by statins, such as the low-density lipoprotein cholesterol (LDL) lowering effects, are not fully understood yet. Here, we used a gut microbiota depleted mouse model to investigate the relation between the gut microbiota and the regulatory property of atorvastatin on blood lipids. Methods: Mice (C57BL/6) with intact gut microbiota or antibiotic induced abiotic mice (ABS) were put on standard chow diet (SCD) or high fat diet (H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…Atorvastatin has greater binding affinity to hepatic HMG‐CoA reductase 29 and belongs to lipophilic statins that can enter into cells by passive diffusion and thereby are widely distributed into different tissues, including heart tissue 30 . In this study, the AT treatment at 3 mg/kg every other day for 12 weeks didn't present lipid‐lowering effect in HFD‐fed mice, due to the much lower dose than the reported dosage range of 20–80 mg/kg on reducing cholesterol in mice in previous experiments 31,32 . Even so, we still observed that atorvastatin ameliorated cardiac remodelling and systolic dysfunction in hypercholesterolaemia mice by a cholesterol‐independent method in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Atorvastatin has greater binding affinity to hepatic HMG‐CoA reductase 29 and belongs to lipophilic statins that can enter into cells by passive diffusion and thereby are widely distributed into different tissues, including heart tissue 30 . In this study, the AT treatment at 3 mg/kg every other day for 12 weeks didn't present lipid‐lowering effect in HFD‐fed mice, due to the much lower dose than the reported dosage range of 20–80 mg/kg on reducing cholesterol in mice in previous experiments 31,32 . Even so, we still observed that atorvastatin ameliorated cardiac remodelling and systolic dysfunction in hypercholesterolaemia mice by a cholesterol‐independent method in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Although the relative abundance of Bacteroidetes decreased significantly after the HFD intervention, the relative abundance of Proteobacteria was observed to increase ( 50 ). In addition, the absolute abundance of the gut microbiota doubled by HFD intervention ( 51 ), which indicated that although the relative abundance of Bacteroidetes was reduced, the total number may not have changed significantly. We observed that SCFAs, BAS, TMAO, and LPS are related to the ability of the gut microbiota to regulate the LDL-C levels via metabolites ( Table 1 ).…”
Section: Microbial Effects On Cholesterol Metabolismmentioning
confidence: 99%
“…Statins are well known as the most commonly used cholesterol-lowering drugs, which can directly reduce plasma cholesterol levels, especially LDL-C ( 110 ), by inhibiting cholesterol synthesis and HMGCR. The cholesterol-lowering effect of statins is closely related to the gut microbiota and can be impaired for the imbalance if gut microbiota ( 12 , 51 ). In addition, different statins, such as atorvastatin, simvastatin, and rosuvastatin, have different effects on different microbiota ( 111 ) and thereby affect MDM ( Table 2 ).…”
Section: Statins-related Potential Pathways Regulating Cholesterol Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…In mice with antibiotic induced microbiome depletion, the lipid lowering effects of atorvastatin were decreased and the expression of hepatic and intestinal cholesterol-regulating genes (Ldlr, Srebp2, and Npc1l1) was altered. 53 In addition to the effects on cholesterol, mice models exhibit changes in intestinal bile acid levels, which the authors hypothesize is due to the gut microbiome. It is postulated that bacteria are needed to enzymatically catalyze the deconjugation of bile acid so that bile can be passively absorbed from the intestine to circulation.…”
Section: Atorvastatinmentioning
confidence: 99%